Bending reinforced concrete beams with glass fiber reinforced polymer bars: an experimental analysis - Fernandes, Tales Viebrantz (2021)
There is a recurring need to construct in places where environmental aggressiveness is very high, such as tidal-splash sites, chemical industries, etc. In these places, steel bars, commonly used for concrete reinforcement, can suffer deterioration, losing cross-sectional area and consequently the resistant capacity. In this regard, Glass Fiber Reinforced Polymers (GFRP) bars can replace steel because of its high strength to harsh environments, low weight and high tensile strength. Thus, this work aimed to compare reinforced concrete beams with steel bars and GFRP bending bars using the procedures indicated in ABNT:NBR 6118 and ACI 440.1R-15, respectively. Experimental three-point flexural tests were performed on six concrete beams, three reinforced with steel bars and three reinforced with GFRP bars. The beams were designed for centered point loads of 23.5 kN, 37.5 kN and 57 kN, and for each load one beam was reinforced in steel and one in GFRP. As main conclusions, it can be said that the beams reinforced with GFRP bars presented greater transverse displacements due to the low modulus of elasticity of this material. In addition, the beams presented rupture loads close to each design load, showing agreement in the recommendations of the two normative documents. Comparing the maximum loads of steel and GFRP beams, ratios of +9.3%, -3.2% and -3% were obtained for beams designed for 23.5 kN, 37.5 kN and 57 kN, respectively. Also, that variations in design loads cause greater variation in the longitudinal reinforcement rate of GFRP bar-beams compared to steel-bar beams.